2002
DOI: 10.1128/aac.46.5.1492-1502.2002
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Gene Regulator ( agr ) Locus in Geographically Diverse Staphylococcus aureus Isolates with Reduced Susceptibility to Vancomycin

Abstract: The majority of infections with glycopeptide intermediate-level resistant Staphylococcus aureus (GISA) originate in biomedical devices, suggesting a possible increased ability of these strains to produce biofilm. Loss of function of the accessory gene regulator (agr) of S. aureus has been suggested to confer an enhanced ability to bind to polystyrene. We studied agr in GISA, hetero-GISA, and related glycopeptide-susceptible S. aureus isolates. All GISA strains from diverse geographic origins belong to agr grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
312
5
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(341 citation statements)
references
References 39 publications
(58 reference statements)
22
312
5
2
Order By: Relevance
“…In a number of these studies, determinations of agr activity were performed by the analysis of delta-hemolysin production on sheep blood agar; however, this is only a semiquantitative measure (296). Similar results were found by using microarray transcriptional analysis or real-time quantitative PCR to measure RNAIII transcripts in paired isolates (121,269).…”
Section: Accessory Gene Regulator (Agr)supporting
confidence: 52%
See 2 more Smart Citations
“…In a number of these studies, determinations of agr activity were performed by the analysis of delta-hemolysin production on sheep blood agar; however, this is only a semiquantitative measure (296). Similar results were found by using microarray transcriptional analysis or real-time quantitative PCR to measure RNAIII transcripts in paired isolates (121,269).…”
Section: Accessory Gene Regulator (Agr)supporting
confidence: 52%
“…agr group and hVISA/VISA. There initially appeared to be a link between the agr group II locus and VISA (296); however, subsequent studies have demonstrated the VISA phenotype in isolates from other agr groups (369). There does, however, appear to be a link between hVISA/VISA and the expression of agr in S. aureus and a potential association between the agr group and the response to vancomycin therapy (see below).…”
Section: Global Epidemiology and Associated Features Of Hvisa And Visamentioning
confidence: 99%
See 1 more Smart Citation
“…Vancomycin-intermediate expression in S. aureus is mediated by chromosomal mutation(s) (Avison et al, 2002;Pfeltz et al, 2000;Sakoulas et al, 2002; and is not due to horizontal gene transfer of vancomycin-resistance determinants (van) from organisms such as the vancomycin-resistant enterococci. VISA strains harbour a chromosomal mutation(s) that leads to alterations in cellwall synthesis and structure, which are thought to impart resistance by sequestering glycopeptide molecules away from their target (for review, see .…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Two-component systems (TCSs) have recently been shown to affect susceptibility to several antibacterial agents. [6][7][8] TCSs are bacteria-specific signal transduction systems consisting of a sensor histidine kinase and cognate response regulator. In S. aureus, TCSs have been characterized mainly in terms of their effect on virulence factor expression and adaptation to environmental conditions.…”
mentioning
confidence: 99%